Growth and welfare effects of health care in knowledge based economies - Michael Kuhn; Klaus Prettner (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2012)
We consider an endogenous growth model with Blanchard-Yaari-type overlapping generations that is built around four sectors: final and intermediate goods production, an R&D sector and a health care sector. Health care serves to lower mortality and morbidity, the latter being related to participation/productivity in the labor market. We show that, regardless of its finance, the impact of health care on economic growth crucially depends on whether or not it increases employment in the R&D sector. Even if an increasing health care sector reduces the (effective) labor available for production and R&D, it may still fuel R&D employment and economic growth if the increase in aggregate wealth that comes with expanding longevity raises the capital intensity in the final goods sector to an extent that labor shifts to alternative employment in R&D. While numerical assessment indicates that the health sectors of the Euro area economies are too large from a growth perspective, we can establish mild conditions under which an expansion of health care beyond the growth-maximizing level constitutes a Pareto-improvement.
Keywords: I11; O41; O11; 330; Endogenous growth; mortality; (Blanchard) overlapping generations; health care; research and development; sectoral composition; Sterblichkeit; Wirtschaftswachstum; Gesundheitsversorgung; Makroökonomischer Einfluss; Overlapping Generations; Neue Wachstumstheorie